2015
DOI: 10.3390/rs71215853
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Five Satellite-Based Latent Heat Flux Algorithms for Semi-arid Ecosystems

Abstract: Accurate estimation of latent heat flux (LE) is critical in characterizing semiarid ecosystems. Many LE algorithms have been developed during the past few decades. However, the algorithms have not been directly compared, particularly over global semiarid ecosystems. In this paper, we evaluated the performance of five LE models over semiarid ecosystems such as grassland, shrub, and savanna using the Fluxnet dataset of 68 eddy covariance (EC) sites during the period 2000-2009. We also used a modern-era retrospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 77 publications
(122 reference statements)
1
20
0
Order By: Relevance
“…Among them, the Priestly‐Taylor Jet Propulsion Laboratory (PT‐JPL) model proposed by Fisher et al . [] has been widely used to estimate ET because of its minimal requirements for ground‐based measurements and its good performance [ Feng et al ., ; Michel et al ., ; Zhu et al ., ]. For example, Ershadi et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, the Priestly‐Taylor Jet Propulsion Laboratory (PT‐JPL) model proposed by Fisher et al . [] has been widely used to estimate ET because of its minimal requirements for ground‐based measurements and its good performance [ Feng et al ., ; Michel et al ., ; Zhu et al ., ]. For example, Ershadi et al .…”
Section: Introductionmentioning
confidence: 99%
“…Remote sensing-based ET estimation methods fall into two broad categories: (1) empirical/statistical methods that relate ET to some easily obtained satellitederived variables (e.g., radiation, land surface temperature, and vegetation index) and (2) process-based methods, which estimate ET on the basis of the Penman-Monteith equation [Monteith, 1965;Cleugh et al, 2007;Mu et al, 2007Mu et al, , 2011, the Priestley-Taylor approach [Priestley and Taylor, 1972;Fisher et al, 2008], or the residual method of the energy balance equation [Bastiaanssen et al, 1998;Su, 2002;Norman et al, 1995]. Among them, the Priestly-Taylor Jet Propulsion Laboratory (PT-JPL) model proposed by Fisher et al [2008] has been widely used to estimate ET because of its minimal requirements for ground-based measurements and its good performance [Feng et al, 2015;Michel et al, 2016;Zhu et al, 2016]. For example, Ershadi models across 20 flux towers.…”
Section: Introductionmentioning
confidence: 99%
“…LE estimates by the four models showed high correlations with ground observations in humid mild regions such as east of Asia and central Europe, whereas low in arid and cold regions such the Mediterranean region and west of Asia. Compared with other methods, PT-JPL and MS-PT were more identical with ground observations [ 36 , 38 ], especially at East Asia sites. RRS, PT-JPL and MS-PT had negative bias ranging from 10 to 20 W/m 2 at most sites.…”
Section: Resultsmentioning
confidence: 79%
“…Validation by Yao et al (2015) [ 37 ] showed that the MS-PT algorithm had good performance over global forest biomes. Feng et al (2015) [ 38 ] found that the MS-PT algorithm improved LE estimation over global grassland, shrubland and savanna.…”
Section: Methodsmentioning
confidence: 99%
“…Among these methods, modelling provides a powerful tool and is becoming more and more popular (Shugart, ). The Priestly–Taylor Jet Propulsion Laboratory (PT‐JPL) model (Fisher, Tu, & Baldocchi, ), which has a process‐based structure to partition total ET into its different components, is physically sound and rigorous, and has been widely used in previous studies due to its minimal requirements for ground‐based measurements and its good performance (Feng et al, ; Michel et al, ; Zhang et al, ; Zhu et al, ).…”
Section: Introductionmentioning
confidence: 99%